2012
DOI: 10.1111/j.1463-1326.2012.01610.x
|View full text |Cite
|
Sign up to set email alerts
|

Longer term safety of dipeptidyl peptidase‐4 inhibitors in patients with type 2 diabetes mellitus: systematic review and meta‐analysis

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibitors are oral antidiabetic agents that hold the potential of slowing the progress of type 2 diabetes mellitus. Their long-term safety is still a subject of debate. A systematic review of randomized, controlled trials was undertaken to comprehensively profile the safety of chronic treatment of type 2 diabetes mellitus with DPP-4 inhibitors. We searched data sources including MEDLINE, CENTRAL, publishers' and manufacturers' databases. Eligible trials were double-blind, random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 95 publications
(113 reference statements)
7
114
1
7
Order By: Relevance
“…However, it is always difficult to confirm a causal relationship in such observational reports because of the presence of many confounding factors [37] . Pooled analyses of large clinical trials with sitagliptin [34] , vildagliptin [40] and linagliptin [48] (Table 2) as well as data from the two recently published major cardiovascular outcome studies reporting liver safety data with saxagliptin [45] and alogliptin [53] (Table 3) are reassuring. On the contrary, some preliminary data suggested that inhibition of DPP-4 might be beneficial in CLD [74,75] .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, it is always difficult to confirm a causal relationship in such observational reports because of the presence of many confounding factors [37] . Pooled analyses of large clinical trials with sitagliptin [34] , vildagliptin [40] and linagliptin [48] (Table 2) as well as data from the two recently published major cardiovascular outcome studies reporting liver safety data with saxagliptin [45] and alogliptin [53] (Table 3) are reassuring. On the contrary, some preliminary data suggested that inhibition of DPP-4 might be beneficial in CLD [74,75] .…”
Section: Discussionmentioning
confidence: 95%
“…Thus, caution is recommended, especially in patients with advanced cirrhosis for whom the problem of controlling effectively and safely blood glucose becomes more crucial and most often requires insulin therapy. or (% CV)* Sitagliptin 100 mg [26] 157 (73) 170 (37) 150 (55) 103 (67) Saxagliptin 10 mg [42,43] [34] , vildagliptin [40] and linagliptin [48] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,36 Le profil de tolérance et de sécurité des inhibiteurs de la DPP-4 est globalement excellent avec une incidence de manifestations indésirables non significativement différente par rapport à celle du placebo et moindre par comparaison à celle de la metformine (moins de troubles digestifs), des sulfamides (moins d'hypoglycémies) et des thiazolidinediones (moins d'oedème et de prise de poids). 39 Contrairement aux glitazones, les gliptines n'augmentent pas le risque de fractures osseuses et pourraient même être associées à une diminution de ce risque. 40 Une tendance à davantage d'infections bénignes des voies respiratoires supérieures a été rapportée incidemment, 41 mais non confirmée dans la plupart des essais cliniques contrôlés.…”
Section: Inhibiteurs De La Dpp-4 (Gliptines)unclassified
“…40 Une tendance à davantage d'infections bénignes des voies respiratoires supérieures a été rapportée incidemment, 41 mais non confirmée dans la plupart des essais cliniques contrôlés. 39,42 Un risque accru de pancréatite, voire de cancer du pancréas, a également été suspecté, mais sur la base de données rapportées exposées à des biais potentiels. 31 Les données collectées dans les essais cliniques sont rassurantes à cet égard.…”
Section: Inhibiteurs De La Dpp-4 (Gliptines)unclassified